Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen